UPAYA PENINGKATAN MOTIVASI BELAJAR IPS MELALUI METODE PICTURE AND PICTURE KELAS IV SDN 022 SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Najrial '; Sumarno '; Feni Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study was the low student motivation can be seen from the symptoms seen in the fourth grade students are not really in learning, do not want to ask, playing time teacher explains, and would not answer any questions. This study aims to increase the motivation to learn in social studies class IV in SDN 022 Sintong Tanah Putih Rokan Hilir through the application of methods Picture and Picture. This research is a Classroom Action Research (CAR) was conducted in four cycles consisting of stages of action planning, implementation, observation and reflection. Each cycle consists of once meetings. The instrument pengumupulan activity observation sheet data that teachers, students, and motivation to learn. Based on the results, it can be concluded that: 1) Activities of teachers increased from the first cycle to the fourth cycle, it can be seen from the observation, in the first cycle teachers only earn a percentage 60.71%, and increased in the second cycle to 75%. In the third cycle teacher activity increased with the acquisition of the percentage of 92.86% and the increase in cycle IV with a percentage of 100%, 2) Activities of students increased from the first cycle to cycle IV, it can be seen from the observation, in the first cycle of student activity in the classical earn a percentage 50.0% increase in cycle II to 62.86%, the third cycle student activity increased with the acquisition of 77.14% and return increased with the acquisition of the percentage reached 86.67%, 3) students' motivation can be increased by perapan method Picture and Picture from the first cycle to cycle IV, it can be seen from the observation, in the first cycle of students' motivation in the classical obtain the percentage of 42.8% to 60.6 in the second cycle, the third cycle student motivation increases with the acquisition of an average percentage of 72.8% to 83.33% in cycle IV, and 4) the success was achieved dapai influenced by the use of methods Picture and Picture, student activities to become more active, which means students tend to be positive in the learning process given by the teacher.Key Words: Students Motivation, Social Subject, Picture and Picture Method